Attachment and commitment of fans to their sports team: Modelling loyalty Behavior - Azouz, Yazid Ben; Dellech, Dorsaf; Debabi, Mohsen (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to investigate the relationships between attachment, commitment, and loyalty among football fans, while also examining the moderating effect of interactivity in the commitment–loyalty link. The objective is to better understand how emotional connections and digital engagement influence long-term fan behavior. A conceptual model was developed based on an extensive literature review and a preliminary qualitative study. The proposed hypotheses were tested through a quantitative survey conducted with 428 football fans. Data were analyzed using the Partial Least Squares (PLS) method to evaluate the relationships between the variables. The results confirm that fan attachment significantly and positively influences commitment, which in turn fosters loyalty. Furthermore, the level of interactivity between fans and the sports team moderates the relationship between commitment and loyalty, reinforcing the strength of this connection. This research highlights the dual importance of emotional and interactive dimensions in cultivating fan loyalty. It emphasizes that fostering attachment and maintaining meaningful digital engagement are essential strategies for sports organizations aiming to build and sustain fan loyalty. Sports managers should prioritize the integration of social media and digital platforms into their communication strategies. Enhanced interactivity not only strengthens fan commitment but also plays a strategic role in loyalty development, offering a competitive advantage in the management of sports teams.